Prognostic value of three clinical nutrition scoring system (NRI, PNI, and CONUT) in elderly patients with prostate cancer - Li, Shu-ying; Wan, Li-lin; Liu, Yi-fan; Li, Yu-Wei; Huang, Xiang; Liu, Rui-ji (Frontiers in Nutrition, 2024)
BACKGROUND: Most of patients with prostate cancer (PCa) are elderly and have a long course of disease.Preoperative assessment of the patient's clinical nutritional status facilitates early intervention and improves patient prognosis.We assessed the nutritional status of PCa patients utilizing the Nutritional Risk Index (NRI), Prognostic Nutritional Index (PNI), and Controlling Nutritional Status (CONUT) scoring systems. Survival comparisons between groups were conducted using Kaplan-Meier curve analysis and log-rank tests, while Cox proportional hazards regression analysis was employed to identify independent prognostic factors.Furthermore, we implemented bootstrap-based optimism correction methods to validate the scoring systems and applied decision curve analysis to evaluate the non-inferiority of these three clinical nutrition scoring systems relative to the conventional American Joint Committee on Cancer (AJCC) staging.In this study, malnutrition was diagnosed in 31.51% of the patients using the NRI, 13.02% using the PNI, and 88.28% using the CONUT score. After adjusting for confounders, normal nutritional status as defined by NRI and PNI emerged as an independent prognostic factor for prostate-specific antigen progression-free survival (PSA-PFS). However, nutritional status assessed by CONUT inaccurately predicted PSA-PFS. Normal nutritional status, as determined by all three scoring systems, was found to be an independent prognostic factor for progression-free survival (PFS). Following adjustments for optimistic estimates, the C-index for NRI in predicting both PSA-PFS and PFS remained the highest among the three scoring systems. The results of the DCA indicated that the C-index of all three scoring systems was higher than that of AJCC stage. CONCLUSIONS: NRI, PNI and CONUT are convenient and clinically applicable scoring systems. A clinical malnutrition intervention may improve the prognosis of prostate cancer patients.